Molecular phylogeny, phylogeography and evolutionary adaptation of foraging behaviour amongst sympatric patellid limpets along the southern African shoreline - Mmonwa, Kolobe Lucas (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2014)
The southern African shoreline is inhabited by a great diversity of patellid limpets of which most are endemic to South Africa. These limpets have evolved foraging mechanisms that partition ecological resources and reduce interspecific competition, resulting in ecological specialists and generalists. The evolution of ecological specialization or generalization remains poorly understood and there is no agreement on how such evolutionary transitions are correlated with levels of genetic diversity. This study investigated evolutionary correlations between territoriality in foraging and genetic structure of southern African patellid limpets (Cymbula and Scutellastra spp.) using stable Î´13C and Î´15N ratios, mitochondrial and nuclear DNA markers. The outcomes of the study were best rationalized and understood in the context of the scale of analysis in terms of both space and taxonomy. At biogeographic scales and the interspecific level, the stable isotope signatures and genetic structure of these limpets are determined by extrinsic factors such as biogeography and oceanography. However, at the smallest site scales and the intraspecific level, the isotope signatures and genetic diversity of these limpets are significantly correlated to their foraging traits. At large scales, there are no correlations between foraging behaviour and either genetic structure or isotope signature. At smaller scales, territorial Scutellastra foragers display both isotopic enrichment and greater haplotype diversity than congeneric non-territorial foragers. Thus, the isotope signatures and genetic structure of these limpets are determined by intrinsic species-specific response linked to their foraging behaviour. However, this pattern was intriguing as differences between territorial and non-territorial limpets in both isotopic signature and genetic diversity were observed only along the south coast when the same species were compared in other biogeographic regions. The significant interaction effect between foraging behaviour and stable isotope signatures was only observed from the sites within the Agulhas Bank or which are strongly influenced by the Agulhas current. This south enrichment in isotopic ratios is due to the mixing differences between onshore and offshore waters as the Agulhas current moves from east to south. At the generic level, the correlation between foraging behaviour and isotope signatures and genetic structure were particularly profound for Scutellastra species. The molecular phylogeny revealed deep evolutionary divergence between territorial and non-territorial Scutellastra spp. This divergence was concordant with morphological differences in shell shape and radula anatomy between territorial and non-territorial species. A taxonomic review of the scutellastrid spp. is proposed, suggesting possible re-consideration of the genus as two genera characterized by either territoriality or non-territoriality. The divergence between territorial and non-territorial species in both Scutellastra and Cymbula took place approximately in the early Oligocene. Major climatic cooling and decreases in sea level occurred during the Oligocene and this probably exposed much of the lower intertidal zone, increasing new potential habitats and algal availability. The Oligocene exposure of rocky shores and algal abundance in the lower intertidal zone probably elicited resource partitioning amongst these patellid limpets and subsequently, the evolution of territorial and non-territorial species. Analyses of the demographic history of these patellid limpets revealed evidence of post-glacial spatial expansion around the Pleistocene, implying these limpets were at population equilibrium during the dramatic LGM sea temperatures. Thus, these limpets managed to expand their range during dynamic oceanographic oscillations and dramatic sea-level changes in the Pleistocene. This study highlighted the importance of applying ecological traits as a subject to investigate and comprehend the evolutionary ecology of marine herbivores. The foraging traits of these true limpets are reflected in both their stable isotope ratios and genealogy, presumably as an evolutionary consequence of competition.
Keywords: Limpets -- South Africa -- Adaptation; Limpets -- South Africa -- Ecology